2014
DOI: 10.1021/ct5000082
|View full text |Cite
|
Sign up to set email alerts
|

Protonation of DMPC in a Bilayer Environment Using a Linear Response Approximation

Abstract: pH is a very important property, influencing all important biomolecules such as proteins, nucleic acids, and lipids. The effect of pH on proteins has been the subject of many computational works in recent years. However, the same has not been done for lipids, especially in their most biologically relevant environment: the bilayer. A reason for this is the inherent technical difficulty in dealing with this type of periodic systems. Here, we tackle this problem by developing a Poisson-Boltzmann-based method that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(77 citation statements)
references
References 82 publications
4
73
0
Order By: Relevance
“…Previous studies have shown that at pH values <4, the protonation state of the phosphoric acid moiety on the DMPC headgroup contributes significantly to overall membrane charge. [25, 26] The resulting addition of H + to an increasingly positively charged DMPC interface in the presence of desorbed Ca 2+ allows for competitive complexation between the DMPC-Ca 2+ and surface PO3-Ca 2+ . The large increase seen for the calcium containing interface is attributed largely to the increased increase in hydration of the interlayer between the supporting surface and DMPC interface.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that at pH values <4, the protonation state of the phosphoric acid moiety on the DMPC headgroup contributes significantly to overall membrane charge. [25, 26] The resulting addition of H + to an increasingly positively charged DMPC interface in the presence of desorbed Ca 2+ allows for competitive complexation between the DMPC-Ca 2+ and surface PO3-Ca 2+ . The large increase seen for the calcium containing interface is attributed largely to the increased increase in hydration of the interlayer between the supporting surface and DMPC interface.…”
Section: Resultsmentioning
confidence: 99%
“…However, those Amgen in-house compounds had HBD of no more than 5, leading to an only positive relationship between log ER and HBD. Such discrepancy in both systems can be conceivably attributed to the fact that the initial P-gp substrate binding can be enhanced by HBD as illustrated by the pharmacophore models of Penzotti et al [ 47 ], whereas the consequent transport of the substrates into the extracellular environment can be hampered by too many HBDs, plausibly because of the increase in water desolvation energy [ 114 ] and the decrease in membrane fluidity [ 115 ]. As such, a nonlinear relationship between HBD and log ER was yielded consequently.…”
Section: Discussionmentioning
confidence: 99%
“…However, those Amgen in-house compounds had HBD of no more than 5, leading to an only positive relationship between log ER and HBD. Such discrepancy in both systems can be conceivably attributed to the fact that the initial P-gp substrate binding can be enhanced by HBD as illustrated by the pharmacophore models of Penzotti et al [47], whereas the consequent transport of the substrates into the extracellular environment can be hampered by too many HBDs, plausibly because of the increase in water desolvation energy [140] and the decrease in membrane fluidity [141]. As such, a nonlinear relationship between HBD and log ER was yielded consequently.…”
Section: Discussionmentioning
confidence: 99%